Preparation and characterization of gellan gum hydrogel as therapeutic protein delivery for wound healing - Radzali, Ahmad Rasul; Chen, Hui Cheng; Radzi, Rozanaliza; Fong, Michelle Wai Cheng; Mohamad Jaafar, Adila; Pei-Shue, Jason Tsai; Ajat, Mokrish (Penerbit UTM Press, 2023)
Therapeutic proteins like platelet-rich plasma have been used as adjunct therapies for wound healing. The delivery of these proteins may require a special carrier as a controlled release to prolong and optimize the healing effects on the affected tissues. The present study focuses on preparing and characterizing a hydrogel made from gellan gum to act as a scaffold to carry therapeutic proteins intended for wound healing. Fetal bovine serum (FBS) was used as a representative for therapeutic proteins due to its ability to stimulate cell proliferation in vitro. FBS, gellan gum (GG) hydrogel, and FBS-loaded gellan gum hydrogel (GF) were prepared and characterized by the detection of its functional groups through FTIR and elemental analysis through CHNS analyzer, confirming the entrapment of biomolecules of FBS into GG. The protein release study showed a burst release of protein from all GF variants with subsequent gradual slow release over 72 hours period. Cell viability (MTT) assay showed an increasing trend of cell viability percentage with the increasing concentration of FBS loaded into GG hydrogel. The results of this study support the potential use of GG hydrogel as a carrier of therapeutic proteins for wound regeneration.